Restrictions of the freedom of speech in France in the digital technologies era - Xenia A. Ivanova; Alexander A. Stepanov (Правоприменение, 2019)
The subject. The article reveals an understanding of the freedom of speech in French law The purpose of the article is to identify the contents of freedom of speech in the French law and to determine the boundaries of its implementation in the Internet as well as to confirm or refute the hypothesis that both the freedom of speech and the definition of the boundaries of that freedom meets the purposes of protection of human rights. The description of methodology. General scientific methods ‐ analysis, synthesis, induction, deduction, comparison ‐ were used. The authors also use the formal legal interpretation of French judicial decisions and content‐analysis of press.The main results and scope of their application. Freedom of speech is one of the foundations of French society, but it has become necessary to revise a number of rules governing freedom of speech and imposing restrictions due to widespread using of Internet in people’s life. So exceptions from freedom of speech are embedded in national legislation, despite the fact that the basis for the legal regulation of freedom of the media in a democratic society is to ensure non‐interference of the state in the content of production and dissemination of information. In some countries exceptions to freedom of speech are expressed primarily in the form of rules aimed at preventing abuses of freedom of the mass media and serving as a basis for sanctions against media editorial boards. The authors also cite actual examples of the realization of the freedom of speech in France, and draw conclusions about the possibilities for the development of this right. The proposed analysis may be used as a basis for improvement national legislation concerning limitations of freedom of speech.Conclusions. Freedom of speech and freedom of the media are not absolute in France. In order to fulfil its function of protecting and guaranteeing rights and freedoms, the state must pay equal attention both to ensuring freedom of speech (including the independence of the press, access to information) and to defining the limits of this freedom in order to prevent its unlawful abuse. Any freedom turns into chaos without proper boundaries.